Back care programmes: The low participation of target groups and unclear effectiveness as primary prevention - Schneider, Sven; Terris, Darcey; Schiltenwolf, Marcus; Barié, Alexander; Diehl, Katharina (Human Movement, 2011)
Purpose. Back care programmes (BCPs) for the prevention of back pain are widespread in Germany. They are intensively promoted and financed by health insurance organizations. The goal of the conducted research was to investigate whether BCPs adequately reach the targeted risk groups for primary and secondary prevention and whether the interventions employed are effective in reducing work disability and absenteeism due to back pain. Basic procedures. Absenteeism associated with back pain (ICD-10 codes M40-M54) and with participation in a BCP were evaluated based on data from 2004 through 2006 for a random sample of 9,781 persons insured with an mandatory health insurance organization. Main findings. 97% of all BCP participants in 2005 had not received a sick leave certificate due to back pain in the previous year. Furthermore, neither bivariate, nor risk-adjusted logistic regression models demonstrated a significant relationship with BCP participation and the subsequent risk of back pain. Conclusions. Current BCPs show low participation of target groups. The effectiveness in primary prevention of new cases is unclear.
CRIS-Team Scopus Importer:2021-12-06
Keywords: back care programmes; back school; health promotion; low back pain; patient compliance; programme effectiveness